Tax Regulation Tools of Tourism Business in order to Localize the Effects of COVID-19 - Elena SIDOROVA; Svetlana ULYANOVA; Ludmila KORSHUNOVA; Veronika ERSHOVA; Igor MURADOV; Daria SAVINOVA (Communications of International Proceedings, 2022)
The research subjects - the mechanism of tax regulation of tourist industry on the example of foreign countries and the Russian Federation in the conditions of pandemic coronavirus. The aim of the research is to identify the features of tax regulation of tourist industry in Italy, Spain, Switzerland, Costa Rica, the Russian Federation. Although the tax legislation of the Russian Federation does not provide a tax levied on enterprises and organizations engaged in tourist activities or involved in the creation of tourist infrastructure, it has two tax-related instruments: preferential taxation of residents of special economic zones of tourist and recreational type and the collection of resort fee in some Russian regions. The article highlights the types of taxes and levies imposed directly or indirectly on tourist activities. It is established that in total there are 15 taxes and fees associated with tourist activities, which can be classified according to five features: environmental, tourist services, recreation (entertainment), tourism infrastructure, mobility. It is determined that the main reasons preventing the gradual recovery of tourist activity are the periodic appearance of new varieties of COVID-19 and the introduction of restrictions on the reception of tourists. It has been established that the most demanded measures of state support for tourist business include tax exemptions, subsidizing of operating costs, deferrals and privileges on rent payments and non-tax payments. It is concluded that the recovery of the tourism industry requires the adoption of comprehensive and special measures by the state, including tax exemption or tax deferral, support for SMEs or individual participants of the tourism market, such as airlines.
Keywords: tax regulation; tourism; resort fee; residents of special economic zones of tourist and recreational type; the willingness of tourists to pay taxes and/or fees.